Perlindungan Hukum Rahasia Perusahaan melalui Undang-Undang No. 30 Tahun 2000 tentang Rahasia Dagang - Ariyanti Ariyanti (Bhirawa Law Journal, 2021)
One of the company's assets that have high economic value is trade secrets. The object of a company's trade secrets can be in the form of written or unwritten information that must consistently be kept secret and has economic value in order to be able to be used to compete with other business actors. The company owner's efforts to maintain the confidentiality of his company information are very important, because if the party is negligent, the existence of trade secrets can fall as Intellectual Property. This study examines the advantages and disadvantages of protecting company secrets with a trade secret system as well as what efforts the company must make to safeguard and protect company secrets. The research method uses a normative juridical approach. The focus of this approach is to examine library materials including legislation and other literature relevant to the problem. The results of this study are the superiority of company secrets protected by a trade secret system, including an unlimited period of protection; confidentiality will be maintained because access to information is closed. Meanwhile, the drawback is that company secrets will still receive legal protection with trade secret regulations as long as the confidentiality is well maintained, if the trade secret is known by others, then the information will become public property and will no longer be protected. And to ensure that trade secrets in a company are kept confidential, the company can take physical steps and a written agreement.